2011
DOI: 10.1257/aer.101.4.1410
|View full text |Cite
|
Sign up to set email alerts
|

Strike Three: Discrimination, Incentives, and Evaluation

Abstract: Major League Baseball umpires express their racial/ethnic preferences when they evaluate pitchers. Strikes are called less often if the umpire and pitcher do not match race/ethnicity, but mainly where there is little scrutiny of umpires. Pitchers understand the incentives and throw pitches that allow umpires less subjective judgment (e.g., fastballs over home plate) when they anticipate bias. These direct and indirect effects bias performance measures of minorities downward. The results suggest how discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
148
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 21 publications
13
148
1
1
Order By: Relevance
“…Similar to other real life settings, like economy or education, another source of bias are race, origin and ethnicity. Parsons, Sulaeman, Yates, and Hamermesh (2011) found that baseball umpires are more likely to call a pitch a strike if they share the race/ ethnicity of the pitcher. Pope and Pope (2015) showed the prevalence of own-nationality bias in the UEFA Champions League by investigating the ratio of foul calls.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other real life settings, like economy or education, another source of bias are race, origin and ethnicity. Parsons, Sulaeman, Yates, and Hamermesh (2011) found that baseball umpires are more likely to call a pitch a strike if they share the race/ ethnicity of the pitcher. Pope and Pope (2015) showed the prevalence of own-nationality bias in the UEFA Champions League by investigating the ratio of foul calls.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, racial biases have been documented in attitudes to Katrina victims (Iyengar and Hahn, 2007;Harris-Lacewell, Imai and Yamamoto, 2007), and Fong and Luttmer (2009) found racially biased giving against black Katrina victims among respondents who reported subjective feelings of ethnic closeness with whites. See also Munnell et al (1996), Cutler, Glaeser and Vigdor (1999), Altonji and Blank (1999), Bertrand andMullainathan (2004), Pager, Western andBonikowski (2006), Price and Wolfers (2007), and Parsons et al (2009) for evidence of discrimination in housing and labor markets. List (2004) finds statistical discrimination in field experiments on sports card markets.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between distance and over-recognition exhibits a non-linear relationship with a rapid decline in the odds of mistake as distance increases. While the potential for runs to be scored (i.e., run expectancy) did not show any statistically significant effects, doubling the importance of the situation (i.e., an increase of leverage by 1) led to a 1.5 percent increase in the odds of a mistaken strike (p<.05), which, along with the positive effect for attendance (p<.01), contradicts the notion that potential scrutiny should reduce the mistakes by umpires (e.g., Parsons et al, 2011). The results also clearly show that the baseline rate of mistake varies significantly across pitch count-for example, the odds of an umpire mistakenly calling a strike is 62 percent lower when the count is 0-2 (i.e., no balls and two strikes, and thus, a strike would end 19 the at-bast), whereas the odds of over-recognition are 49 percent higher when the count is 3-0 (i.e., three balls and no strikes, a count that is known for generous strike calls)-validating the inclusion of count dummies.…”
mentioning
confidence: 78%
“…3 Umpires are called upon to make instantaneous judgments of quality without the benefit of deliberation (e.g., Rainey et al 1989), creating the possibility that subjective aspects of the game will bias their judgment. For example, recent studies have shown that professional sports officials were biased toward players of their own race (Price and Wolfers 2010;Parsons et al 2011) The final reason that umpiring is an ideal setting to assess status bias is because umpires have strong incentives to call the strike zone as accurately and as consistently as possible. MLB has made recent efforts to closely monitor and evaluate their accuracy.…”
mentioning
confidence: 99%